Epigenetic Regulation of Macrophage Polarization in Cardiovascular Diseases - Sumra Komal; Sheng-Na Han; Liu-Gen Cui; Miao-Miao Zhai; Yue-Jiao Zhou; Pei Wang; Muhammad Shakeel; Li-Rong Zhang (MDPI AG, 2023)
Cardiovascular diseases (CVDs) are the leading cause of hospitalization and death worldwide, especially in developing countries. The increased prevalence rate and mortality due to CVDs, despite the development of several approaches for prevention and treatment, are alarming trends in global health. Chronic inflammation and macrophage infiltration are key regulators of the initiation and progression of CVDs. Recent data suggest that epigenetic modifications, such as DNA methylation, posttranslational histone modifications, and RNA modifications, regulate cell development, DNA damage repair, apoptosis, immunity, calcium signaling, and aging in cardiomyocytes; and are involved in macrophage polarization and contribute significantly to cardiac disease development. Cardiac macrophages not only trigger damaging inflammatory responses during atherosclerotic plaque formation, myocardial injury, and heart failure but are also involved in tissue repair, remodeling, and regeneration. In this review, we summarize the key epigenetic modifications that influence macrophage polarization and contribute to the pathophysiology of CVDs, and highlight their potential for the development of advanced epigenetic therapies.